Caste, class, and power : changing patterns of stratification in a Tanjore village - Beteille, Andre (Delhi ; New York : Oxford University Press, 2002)
Study of Thanjavur District.
Revision of the author's thesis (Ph. D.--University of Delhi).
Includes bibliographical references and index.
Keywords: Caste -- India -- Thanjavur (District).; Social classes -- India -- Thanjavur (District).; Peasants -- Political activity -- India -- Thanjavur (District).; Power (Social sciences).